2020
DOI: 10.1093/jac/dkaa070
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with tenofovir diphosphate concentrations in dried blood spots in persons living with HIV

Abstract: Objectives To determine factors associated with interindividual variability in tenofovir diphosphate (TFV-DP) concentrations in dried blood spots (DBSs) among persons living with HIV (PLWH). Methods PLWH who were at least 18 years old and taking tenofovir disoproxil fumarate-containing ART were prospectively recruited and enrolled from a clinical cohort and followed longitudinally (up to three visits over 48 weeks). With log-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 35 publications
1
17
1
Order By: Relevance
“…We will also investigate how factors like BMI, sex, and drug-drug interactions in uence intracellular TFV-DP drug levels. (32) We will validate the RESTRICT assay to meet established Clinical Laboratory Improvement Amendments criteria to enable reporting of results to clients. The RESTRICT assay could be used to evaluate the role of adherence in treatment failure and emergence of drug resistance among people living with HIV.…”
Section: Discussionmentioning
confidence: 99%
“…We will also investigate how factors like BMI, sex, and drug-drug interactions in uence intracellular TFV-DP drug levels. (32) We will validate the RESTRICT assay to meet established Clinical Laboratory Improvement Amendments criteria to enable reporting of results to clients. The RESTRICT assay could be used to evaluate the role of adherence in treatment failure and emergence of drug resistance among people living with HIV.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously shown (1) the impact of fat mass or BMI on physical function performance [ 31 , 32 ] and (2) a strong association between BMI and TFV-DP in DBS among a large clinical cohort of PWH [ 33 , 34 ]. Here, higher TFV-DP in DBS were associated with slower chair rise time, slower time to complete a 400-meter walk, and SPPB impairment.…”
Section: Discussionmentioning
confidence: 99%
“…As noted, HIV VL and DBS were collected simultaneously throughout the study. Dried blood spots (DBS) were assayed using a longitudinal case–control extension strategy, where PWH who had a detectable HIV VL (>20 copies/mL) at any of their study visits were considered to be cases, and those with viral suppression at all study visits where considered controls, as previously reported in this cohort 1,8,9 …”
Section: Methodsmentioning
confidence: 99%
“…Among the available measures of ART adherence are self‐report, pharmacy refills, electronic monitoring, directly observed therapy (DOT), electronic pill boxes, and pharmacologic biomarkers, such as drug concentrations in urine, hair, and dried blood spots (DBS) 7 . Previous research on tenofovir diphosphate (TFV‐DP) in DBS, a measure of cumulative ART adherence and exposure in PWH taking tenofovir‐based regimens, has demonstrated that this adherence biomarker is strongly associated with viral suppression, is predictive of future viremia, and is influenced by several biological, demographic, and social factors 1,8–11 . Despite the potential simplicity of ART, PWH may be taking numerous additional medications, including over‐the‐counter (OTC) agents, which can increase the burden on medication adherence.…”
Section: Introductionmentioning
confidence: 99%